Year-Round Movements of Sooty Terns (Onychoprion fuscatus) Nesting Within One of the Atlantic’s Largest Marine Protected Areas - Reynolds, S. James; Wearn, Colin P.; Hughes, B. John; Dickey, Roger C.; Garrett, Lucy J. H.; Walls, Sean; Hughes, Fay T.; Weber, Nicola; Weber, Sam B.; Leat, Eliza H. K.; Andrews, Kenickie; Ramos, Jaime A.; et al. (Frontiers in Marine Science, 2021)
Seabirds are among the most threatened birds as a result of acute exposure to many anthropogenic threats. Their effective conservation requires a detailed understanding of how seabirds use marine habitats. Recently, one of the largest no-take marine reserves in the Atlantic was designated in tropical waters surrounding Ascension Island, on which the largest Atlantic population of sooty terns (Onychoprion fuscatus) breeds. Although they are the most abundant tropical seabird, they appear to have suffered marked population declines on Ascension Island as they have elsewhere. Here, we describe year-round movements and habitat use of male and female sooty terns between 2011 and 2015. On average, birds traveled 47,000 km during their 8 months of migration, during which they remained within 2,900 km of the island. They spent most of the day and night in flight, only touching down briefly on the ocean most likely to feed. Habitat suitability models successfully predicted foraging ranges of birds and their at-sea distributions varied considerably between seasons, years and sexes. Considerable variation in range overlap between birds and the new marine protected area (MPA) suggests that similar such studies of other marine taxa are urgently needed. The range of sooty terns mainly falls in the high seas outside of the new MPA, highlighting the very large areas that many oceanic seabirds forage across and the challenges their conservation present.